2008
DOI: 10.1080/02640410802409675
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake and body composition of football players during the holy month of Ramadan

Abstract: Healthy young male football players who were either fasting (n = 59) or not fasting (n = 36) during the month of Ramadan were studied. Body mass, body composition, and dietary intake were assessed at each time point. Energy intake was relatively stable in the fasting participants, but there was a small decrease of approximately 0.7 kg in body mass during Ramadan. Mean daily energy intake increased from 14.8 MJ (s = 2.9) to 18.1 MJ (s = 3.2) during Ramadan in non-fasting participants, with concomitant increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 39 publications
4
58
1
1
Order By: Relevance
“…However, the time frame between finishing a meal and undertaking training might cause some difficulties, as some athletes cannot tolerate strenuous exercise soon after eating, and this may result in the athlete restricting food intake before training. The use of night-time snacks to meet any energy and fluid deficits may therefore be an important adjunct to dietary intake during Ramadan 26 64 65…”
Section: Practical Implicationsmentioning
confidence: 99%
“…However, the time frame between finishing a meal and undertaking training might cause some difficulties, as some athletes cannot tolerate strenuous exercise soon after eating, and this may result in the athlete restricting food intake before training. The use of night-time snacks to meet any energy and fluid deficits may therefore be an important adjunct to dietary intake during Ramadan 26 64 65…”
Section: Practical Implicationsmentioning
confidence: 99%
“…This may be accompanied by a reduction in the intake of carbohydrate to compensate for an increased intake of fat and protein, resulting in a relatively constant energy intake (El Ati, Beji, & Danguir, 1995). A change in body mass may or may not be observed (see Maughan, Bartagi, Dvorak, & Zerguini, 2008), and there may be an increased reliance on fat oxidation (El Ati et al, 1995), a decrease in the basal metabolic rate (Husain, Duncan, Cheah, & Ch'ng, 1987) and in the resting metabolic rate as measured in the afternoon (Sweileh, Schnitzler, Hunter, & Davis, 1992). However, any changes in body mass, nutrient intake (carbohydrates, fats, protein, vitamins, and minerals), and nutritional status that take place during the Ramadan fast may depend on the level of physical activity of the individuals (Chaouachi et al, 2007;Ramadan, Moussa, & Telahoun, 1994).…”
mentioning
confidence: 97%
“…For instance, Al-Hourani HM surveys showed that body weight and BMI decreased noticeably during fasting periods (8).The reduction of body weight has been reported quite repeatedly, but the connection between weight loss and body fat reduction is not often studied (9). Inconsistent findings have also been reported, regarding the effects of fasting on body composition (10,11). Some investigations did not find any significant changes in body weight or body composition during Ramadan (10)(11)(12).…”
Section: Contextmentioning
confidence: 82%
“…Inconsistent findings have also been reported, regarding the effects of fasting on body composition (10,11). Some investigations did not find any significant changes in body weight or body composition during Ramadan (10)(11)(12). Effect of Ramadan on biochemical parameters is still a debatable issue.…”
Section: Contextmentioning
confidence: 82%